Proton therapy for isolated local regional recurrence of breast cancer after mastectomy alone - Laughlin, Brady S.; Bhangoo, Ronik S.; Niska, Joshua R.; Thorpe, Cameron S.; Girardo, Marlene E.; Anderson, Justin D.; Kosiorek, Heidi E.; McGee, Lisa A.; Hartsell, William F.; Chang, John H.; Rossi, Carl J.; Tsai, Henry K.; et al. (Frontiers in Oncology, 2022)
Purpose/Objectives To assess adverse events (AEs) and disease-specific outcomes after proton therapy for isolated local-regional recurrence (LRR) of breast cancer after mastectomy without prior radiotherapy (RT). Materials/Methods Patients were identified from a multi-institutional prospective registry and included if diagnosed with invasive breast cancer, initially underwent mastectomy without adjuvant RT, experienced an LRR, and subsequently underwent salvage treatment, including proton therapy. Follow-up and cancer outcomes were measured from the date of RT completion. Results Nineteen patients were included. Seventeen patients were treated with proton therapy to the chest wall and comprehensive regional lymphatics (17/19, 90%). Maximum grade AE was grade 2 in 13 (69%) patients and grade 3 in 4 (21%) patients. All patients with grade 3 AE received > 60 GyE (p=0.04, Spearman correlation coefficient=0.5). At the last follow-up, 90% of patients were alive with no LRR or distant recurrence. Conclusions For breast cancer patients with isolated LRR after initial mastectomy without adjuvant RT, proton therapy is well-tolerated in the salvage setting with excellent loco-regional control. All grade 3 AEs occurred in patients receiving > 60 GyE.